Realization of Innovative Tasks in the Public Local Government and Self-Government in Kazakhstan - S, Mukhtаrovа K.; R., Mouly P.; T, Myltykbayeva A.; E, Mukhtar E. (Farabi Journal of Social Sciences, 2019)
Abstract. One of key problems of modern Kazakhstan, which are important for further democratic development of the country, is creation of local self-government. The rights of citizens to local self-government proclaimed the Constitution of 1995 still remain not implemented. Several attempts to draft the bill on local self-government were made in recent years. The main obstacle is lack of unity in understanding of local self-government among the political and public numbers of the country. Key words: public local government, self-government, innovative tasks, republican and local authorities, direct and indirect state, business environment regulation.